Collaborative Governance Dalam Pengembangan Pariwisata “Waduk Bendo” di Desa Bendo, Kecamatan Kapas, Kabupaten Bojonegoro - Nanda, Della Dwi; Suprastiyo, Ahmad; Junadi, Junadi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The concept of collaborative governance explains that basically the need to collaborate arises from the interdependent relationship between parties. The success of the tourism development process cannot be separated from the attachment between stakeholders. This research aims to describe how collaborative governance in the process of developing Bendo reservoir tourism. This research uses descriptive qualitative research methods and data collection techniques using field studies conducted directly to the research location through observation, interviews and documentation. This research uses the theory put forward (Ratner, 2012), namely: Identifying Obstacles and Opportunities, Debating Strategies For Influence, Planning Collaborative Action and refined with the success criteria (Goldsmith and Kettl, 2009: 135-136) of a collaboration in governance, namely Networked Structure, Commitment to a Common Purpose, Trust Among The Participants, Governance, Access to Authority, Distributive Accountability / Responsibility, Information Sharing, Access to Resources. The results showed that collaborative governance in the development of bendo reservoir tourism in bendo village, Kapas sub-district, Bojonegoro Regency has not run optimally. This can be seen from the success indicators that are not achieved, namely the absence of official written regulations that bind the collaboration process that is carried out, commitment in achieving goals that are not carried out by all stakeholders involved, limited human resources and lack of budget funds to build infrastructure. Keywords: Collaborative Governance, Stakeholders, Tourism Development ABSTRAK Konsep collaborative governance menjelaskan bahwa pada dasarnya kebutuhan untuk berkolaborasi muncul dari adanya hubungan saling ketergantungan antar pihak. Keberhasilan proses pengembangan wisata tidak lepas dari adanya keterikatan antara stakeholders. Penelitian ini bertujuan untuk untuk mendeskripsikan bagaimana collaborative governance dalam proses pengembangan wisata waduk Bendo. Penelitian ini menggunakan metode penelitian kualitatif deskriptif danteknik pengumpulan data menggunakan studi lapangan yang dilakukan secara langsung terjun ke lokasi penelitian melalui observasi, wawancara dan dokumentasi. Penelitian ini menggunakan teori yang dikemukakan (Ratner,2012) yaitu : Identifying Obstacles and Opportunities, Debating Strategies For Influence, Planning Collaborative Action dan disempurnakan dengan kriteria keberhasilan(Goldsmith dan Kettl, 2009:135-136) sebuah kolaborasi dalam governance, yaitu Networked Structure, Commitment to a Common Purpose, Trust Among The Participants, Governance, Access to Authority, Distributive Accountability / Responsibility, Information Sharing, Access to Resourch.Hasil penelitian menunjukkan bahwa collaborative governance dalam pengembangan wisata waduk bendo di desa bendo Kecamatan Kapas Kabupaten Bojonegoro belum berjalan optimal. Hal ini dilihat dari indicator keberhasilan yang tidak tercapai yaitu tidak adanya peraturan tertulis resmi yang mengikat proses kolaborasi yang dijalankan, komitmen dalam mencapai tujuan yang tidak dilakukan oleh semua stakeholders yang terlibat, keterbatasan sumber daya manusia serta minimnya anggaran dana untuk membangun sarana prasarana. Kata kunci : Collaborative Governance, Stakeholders, Pengembangan Wisata